‘Ca. Phytoplasma pruni’ and ‘Ca. Phytoplasma meliae’ are affecting plum in Argentina - Bongiorno, Vanina Aylén; Alessio, Florencia Ivette; Curzel, Viviana Noemi; Nome Docampo, Claudia; Fernandez, Franco Daniel; Conci, Luis Rogelio (Springer, 2021)
We report for the first time the presence of phytoplasmas in association with Plum (Prunus domestica) yellowing in Argentina. Molecular analysis of 16S rDNA gene sequence (RFLP, phylogeny) reveals the existence of two different 16Sr-subgroups, 16SrIII-B and novel 16SrXIII-L. These results contribute to a better understanding of the diversity of phytoplasmas associated with Prunus genera in South America.